Penyelesaian Klaim Pada Asuransi Kendaraan Bermotor Melalui Badan Mediasi dan Arbitrase Asuransi Indonesia (BMAI) - Sulma Sofinatus Sofiyatun; Abdul Mujib (Cakrawala Repositori IMWI, 2023)
Insurance or about liability is an agreement between two or more parties in which the insurer binds himself to the insured by accepting insurance premiums to provide compensation to be taken due to loss, damage or expected loss, or take the law to third parties who may suffer from events that are not absolutely covered by the insured, or provide a payment based on the death or life of someone who is covered (Article 1 sentence (1) of Law No. 1992). In a motor vehicle insurance agreement, it is not closed to the possibility of disputes, these disputes are usually within the period of claims caused by the insured and the insurer. One way to resolve the dispute is through the Indonesian Insurance Mediation Warm Up (BMAI). The Indonesian Insurance Mediation Agency (BMAI) is an independent body that has independent mediators assigned to conduct insurance claim disputes resolved between the insured and the underwriter. An insurance claim dispute is a dispute between the insured and the insurer that respects one of the parties does not carry out the agreement that has been made with all due consideration or even because there is a party who defaults, to the detriment of one of the parties. The procedure for resolving motor vehicle insurance claim disputes goes through 2 stages, namely the mediation stage and the adjudication stage. If the dispute can best be resolved at the mediation stage then resolve the dispute, otherwise if the dispute cannot be resolved at the mediation stage then the settlement is drawn to the adjudication stage. Not all claim disputes can be resolved through the Indonesian Insurance Agency Mediation (BMAI) because there are conditions that must be met by the insured. Even though the conditions have been met, it does not rule out the possibility that the dispute over the insurance claim process through Warms Up Indonesian Insurance Mediation (BMAI) will be constrained.